2007
DOI: 10.1111/j.1365-2222.2007.02836.x
|View full text |Cite
|
Sign up to set email alerts
|

Increasing trend in atopy markers prevalence in a Croatian adult population between 1985 and 1999

Abstract: An increasing trend in the prevalence of concurrently elevated total IgE and positive atopic symptoms was found in the Croatian adult male population between 1985 and 1999, but not in the female population. Sex differences responsible for the production and regulation of IgE were suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…We included the following covariates that were either significant on univariate testing (Table 1), or important for allergic sensitization or atopic diseases based on the literature: age (18-24, 25-39, 30-34, and 35-39 years), education (primary school or lower, junior middle school, high school or higher), occupation (farmer/non-farmer), cockroach in house (none, occasional, some, or many), and tobacco exposure (passive exposure for women)3, 27. We also tested the linear trends across quartiles of adiposity measures and lipid levels, and across BMI categories.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We included the following covariates that were either significant on univariate testing (Table 1), or important for allergic sensitization or atopic diseases based on the literature: age (18-24, 25-39, 30-34, and 35-39 years), education (primary school or lower, junior middle school, high school or higher), occupation (farmer/non-farmer), cockroach in house (none, occasional, some, or many), and tobacco exposure (passive exposure for women)3, 27. We also tested the linear trends across quartiles of adiposity measures and lipid levels, and across BMI categories.…”
Section: Methodsmentioning
confidence: 99%
“…Over recent decades, the worldwide prevalence of obesity,1 allergic sensitization and atopic diseases2, 3 has risen dramatically. There is increasing evidence that excess adiposity and metabolic syndrome are associated with chronic systemic inflammation4 and asthma 5, 6.…”
Section: Introductionmentioning
confidence: 99%
“…Sensitisation to common allergens and development of typical symptoms of an allergic disease usually occurs in childhood and adolescence. However, a recent study has shown a signifi cant increase in the prevalence of atopy markers (IgE antibodies, positive skin prick test) in Croatian adult population in the period between 1985 and 1999, particularly in men (43). The reasons for the fi rst occurrence of atopic diseases in adulthood are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of atopic disorders such as asthma, allergic rhinoconjunctivitis, and atopic eczema has increased over the past two decades in many countries including Croatia (1). Atopy is a complex genetic disease that results from the interplay between gene variants and environmental influences (2).…”
mentioning
confidence: 99%